Tracing Transnationalism and Hybrid Identities in Aleksandar Hemon’s The Making of Zombie Wars - Nina Bostič Bishop (Acta Neophilologica, 2019)
Transnationalism is a current reality as globalisation has accelerated by the never before experienced boost in the development of technology, transport and telecommunications. The modern era is also characterised by migrations - voluntary and involuntary, but most of today’s transmigrants do not live the exilic lives once lived by migrants, longing for their homeland. Instead, they live in an in-between space – the host country and the homeland, where the mixing of cultures takes place. Although these zones have often been idolized in the recent literature, the lives of many transmigrants are characterised by feelings of loss, displacement and trauma. The present article attempts to map Bosnian-American author Aleksandar Hemon as a transnational diasporic writer by tracing the features of transnationalism in his life and his novel The Making of Zombie Wars. It will also position that several of the migrant characters in the novel are hybrid identities, battling the consequences of displacement, trauma and mobility, following the ideas of Homi Bhabha and Jopi Nyman. It will explore the processes as they occur in spaces in-between.